2020
DOI: 10.1371/journal.pone.0232331
|View full text |Cite
|
Sign up to set email alerts
|

Research on a floating thermoelectric power generator for use in wetland monitoring

Abstract: A floating power generation device is designed and fabricated to overcome the power supply limitations of wireless sensor networks for environmental monitoring. Once there is a temperature difference between the upper surface exposed to sunlight and the lower surface in the water, the device is capable of generating power while floating in the wetland environment. Fresnel lenses were applied to concentrate solar irradiation on a selective absorbing coat. Meanwhile two vertical axis rotors were used to cool the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…When the input voltage reached 180 mV, 1,620 μW of power was produced by the TEG and 336.9 μW of power could be harvested into a rechargeable battery [17]. Although there are research examples like this, the rigid-TEG's outer surface makes it easier to utilize on flat surfaces, so it is mainly used for structural and environmental monitoring [6][7][8]18].…”
Section: Inorganic Tegsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the input voltage reached 180 mV, 1,620 μW of power was produced by the TEG and 336.9 μW of power could be harvested into a rechargeable battery [17]. Although there are research examples like this, the rigid-TEG's outer surface makes it easier to utilize on flat surfaces, so it is mainly used for structural and environmental monitoring [6][7][8]18].…”
Section: Inorganic Tegsmentioning
confidence: 99%
“…Using a wind speed of less than 3.3 m/s above the water surface, the device's cooling system could be driven, which increased the output power by 10.96 %. This new power supply system is waterproof and can float stably on the water, allowing for monitoring of various wetland environments [18]. Mukaida et al reported the design and fabrication of gram-scale polymer-based thermoelectric modules fabricated by laminating ultrathin semi-dry PEDOT:PSS films with Ni foil.…”
Section: Structure/environment Monitoring Systemsmentioning
confidence: 99%
“…(2) reduction of the impact of the external environment on TENGs [38,39], (3) enhancement of the surface charge density, including active charge pumping and intercalation of a charge trap layer [40,41], and (4) increase of the number of TENG units [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…It could be observed that the voltage across the sensing node was in dynamic balance during the continuous power supply process, showing that the designed TEHG can complete the purpose of powering the IoT node. The TEHG designed in this paper can meet the needs of long monitoring time and environmental adaptability in some special environments, such as grasslands, plateaus, [ 35 ] wetlands, [ 36 ] offshore, tunnels, and roofs in cities. [ 37 ] Therefore, TEHG can provide continuous energy supply for environmental monitoring sensor nodes in unattended or inaccessible locations.…”
Section: Introductionmentioning
confidence: 99%